A mediação na formação de uma comunidade de ensino, aprendizagem e trabalho - Antunes, Ana Silvia Martins Montrezol (2008)
In order to understand how a Virtual Community of Teaching and Learning develops into a Virtual Community of teaching, learning and work, this study was to undertake an analysis, from theoretical benchmarks on the issues of learning and technology, discussed by Garrison and Anderson (2001, 2003 and 2005); of elements that make up the Interpersonal Metafunction, developed by Halliday (1991), and of elements of Appraisal addressed by Eggins (1997) and White (2000) from Martin (1994). They were also used for this analysis, the functions of mediation conducted by Gervai (2007) and assumptions and andragocics concepts, established by Chotguis (2007) and Tavares-Silva (2006), respectively. The corpus for conducting the search were the messages posted to the informal forum Coffee and the forum Module 1 and 2 to 1 and Stage forum Module 1 to 2 nd. phase, which make up the Training Course for Management and Improvement Programa Bolsa Família in the State of Sao Paulo. The analysis included three distinct phases, observed in Virtual Community: Stage 1 - The first contact the student / participant in the community; Stage 2 -. The Community after its reformulation, and Stage 3 - The community near its end. The goal of these stages was explain how the mediation takes place at the beginning of the work of the community, as the mediator contributes to the formation and strengthening of a Virtual Community of Learning, Education and Labor and as the students / participants interact with each other. The aim higher, to examine the issues related to each stage, it was understood as a Virtual Community of Learning and Teaching develops into a Commonwealth of Learning, Education and Labor. The mediations were examined in each of these stages, as well as the actions of the students / participants now also carrying out mediation in the virtual environment for learning